2016
DOI: 10.1039/c6cc04242b
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-small Ge1−xSnx quantum dots with visible photoluminescence

Abstract: GeSn alloy quantum dots (QDs) were synthesized with sizes ranging from 1-3 nm exhibiting visible orange-red photoluminescence. Composition dependent optical properties were characterized and supported by theoretical calculations. Structural analysis suggests the QDs are diamond cubic phase, characteristic of GeSn thin films and nanocrystals (NCs) reported to date.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
64
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(68 citation statements)
references
References 24 publications
3
64
0
1
Order By: Relevance
“…[6][7][8][9][10] The long-chain aliphatic native ligands that are typically present from the nanocrystal synthesis (e.g., C18 oleylamine) impart solution dispersibility in nonpolar organic solvents; however, many potential applications of Ge nanocrystals require the exchange of such native ligands with new ligands that will, for example, improve their charge mobility and conductivity in nanocrystal solids, 11 or allow them to be dispersed in polar, biologically relevant media. 12 Beginning with the work of Boyle et al in 2005, 13 synthesizing colloidal Ge nanocrystals by the high-temperature chemical reduction of Ge(II) and/or Ge(IV) precursors in long-chain aliphatic primary amines has become common practice, 12,[14][15][16] resulting in nanocrystals passivated by surface-coordinated amine ligands. While only a few ligand exchange reactions on these Ge nanocrystals have been reported thus far, it has been demonstrated that the native primary amine ligands can be at least partially exchanged with thiols, 12,17 polyethyleneimine, 11 and polysulfides 18 via room temperature exchange reactions.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] The long-chain aliphatic native ligands that are typically present from the nanocrystal synthesis (e.g., C18 oleylamine) impart solution dispersibility in nonpolar organic solvents; however, many potential applications of Ge nanocrystals require the exchange of such native ligands with new ligands that will, for example, improve their charge mobility and conductivity in nanocrystal solids, 11 or allow them to be dispersed in polar, biologically relevant media. 12 Beginning with the work of Boyle et al in 2005, 13 synthesizing colloidal Ge nanocrystals by the high-temperature chemical reduction of Ge(II) and/or Ge(IV) precursors in long-chain aliphatic primary amines has become common practice, 12,[14][15][16] resulting in nanocrystals passivated by surface-coordinated amine ligands. While only a few ligand exchange reactions on these Ge nanocrystals have been reported thus far, it has been demonstrated that the native primary amine ligands can be at least partially exchanged with thiols, 12,17 polyethyleneimine, 11 and polysulfides 18 via room temperature exchange reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Data confirming such high Sn concentrations in Ge 1−x Sn x with high crystallinity have only been rarely described in literature with limited information about their actual homogeneity with maximum Sn contents of ~30 %. 25,26,27,35,36,37 The thermal stability of thin films with different composition is reported, but these reports do usually not cover higher tin contents >15 %, the heat treatment is limited to short time, e.g. by rapid thermal annealing, and the films are usually highly strained.…”
Section: Introductionmentioning
confidence: 99%
“…They also used time-resolved PL at low (15 K) and ambient temperatures to further understand carrier dynamics. [112][113] PL lifetimes at 15 K were found to be 3-27 μs, three orders of magnitude slower than at room temperature, owing to slow recombination of carriers in surface traps and spin-forbidden dark excitons. Temperature effects on the PL of very thin Ge1-xSnx films have also been studied, showing a monotonic thermal PL quenching despite the indirect nature of the band gap.…”
Section: Introductionmentioning
confidence: 90%